Pengaruh Media Pembelajaran Genially terhadap Hasil Belajar Bahasa Indonesia Siswa Kelas X di SMK Al-Amanah Salem - Alkindi Gagah Pracaya Maulana; Eva Gustiana (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to determine the effect of the use of Genially learning media on the Indonesian language learning outcomes of 10th-grade students at SMK Al-Amanah Salem. The background of this study is based on the low interest and motivation of students in learning Indonesian, which has so far been dominated by conventional methods. Genially, as an interactive technology-based learning media, is believed to be able to provide a more interesting, creative learning atmosphere, and in accordance with the needs of the digital generation. The research method used is a quantitative method with an experimental design of One Group Pretest-Posttest Design, where the research sample was determined through a purposive sampling technique. The study population included all 10th-grade students in the Automotive Engineering and Software and Game Development departments in the 2023/2024 academic year. Data collection instruments in the form of observation, questionnaires, documentation, and tests were used to measure student learning outcomes before and after treatment. The results of the study showed a significant increase in student learning outcomes after the implementation of Genially learning media. A comparison of pretest and posttest scores showed an increase in the average score, which indicates that students were better able to understand Indonesian language material after participating in learning using this interactive media. In addition, student responses to the use of Genially were very positive. Students felt more motivated due to the varied presentation of the material, attractive visuals, and interactive features that encouraged active engagement in the learning process. Based on these findings, it can be concluded that the use of Genially media in Indonesian language learning has a positive effect on improving student learning outcomes.